2010
DOI: 10.1126/scisignal.2001158
|View full text |Cite
|
Sign up to set email alerts
|

HLA Class I Molecules Partner with Integrin β 4 to Stimulate Endothelial Cell Proliferation and Migration

Abstract: Among transplant recipients, those who produce antibodies against the donor's human leukocyte antigens (HLAs) are at higher risk for antibody-mediated rejection and transplant vasculopathy, which is a progressive, vasculo-occlusive disease that results in ischemic injury and deterioration of organ function. Antibodies against HLA class I (HLA-I) molecules are thought to contribute to transplant vasculopathy by triggering signals that elicit the activation and proliferation of endothelial cells. Here, we demons… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

6
92
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
3
2
2

Relationship

1
6

Authors

Journals

citations
Cited by 95 publications
(101 citation statements)
references
References 56 publications
6
92
0
Order By: Relevance
“…26 -28,37 Moreover, the concomitant inhibition of anti-HLA mAb-induced MMP2 activation, mitogenic signaling, SMC proliferation, and neointimal hyperplasia by the MMP inhibitor Ro28-2653 is consistent with recent observational studies from Lutz et al, 24 Tsukioka et al, 25 and Hariya et al, 26 suggesting a strong association between MMP2 and transplant vasculopathy. These data and reports from Reed et al [11][12][13][14]35 indicate that multiple signaling pathways act together to trigger the mitogenic effect mediated by W6/32 mAbs. Note that the anti-HLA mAb concentration used in our experiments for triggering SMC proliferation was lower than that used by Reed, 35 but the dose-response curve showed that the W6/32 mAb concentration used here induces a proliferation in SMCs similar to that obtained with higher dose ( Figure IV in the online-only Data Supplement).…”
Section: Galvani Et Al Mmp2 and Nsmase2 In Transplant Vasculopathy 2729mentioning
confidence: 48%
See 3 more Smart Citations
“…26 -28,37 Moreover, the concomitant inhibition of anti-HLA mAb-induced MMP2 activation, mitogenic signaling, SMC proliferation, and neointimal hyperplasia by the MMP inhibitor Ro28-2653 is consistent with recent observational studies from Lutz et al, 24 Tsukioka et al, 25 and Hariya et al, 26 suggesting a strong association between MMP2 and transplant vasculopathy. These data and reports from Reed et al [11][12][13][14]35 indicate that multiple signaling pathways act together to trigger the mitogenic effect mediated by W6/32 mAbs. Note that the anti-HLA mAb concentration used in our experiments for triggering SMC proliferation was lower than that used by Reed, 35 but the dose-response curve showed that the W6/32 mAb concentration used here induces a proliferation in SMCs similar to that obtained with higher dose ( Figure IV in the online-only Data Supplement).…”
Section: Galvani Et Al Mmp2 and Nsmase2 In Transplant Vasculopathy 2729mentioning
confidence: 48%
“…9 -11 HLA alloantibodies have been implicated in chronic allograft rejection and vascular cell proliferation, [13][14][15]17 but thus far their mechanism of action is only partly understood. [13][14][15] The rationale of this study came from our previous work on the stress-induced sphingomyelin/ceramide pathway, which indicated a role for MMPs (namely, MT1-MMP and MMP2) and nSMase2 in stress-induced SMC proliferation. 19,20 We hypothesized that this signaling may also be triggered by anti-HLA mAbs, which behave like stress-inducing agents.…”
Section: Galvani Et Al Mmp2 and Nsmase2 In Transplant Vasculopathy 2729mentioning
confidence: 99%
See 2 more Smart Citations
“…It is postulated that TG is the consequence of continuous peritubular glomerulitis and capillaritis or that low levels of DSA and complement are present in the graft, but current assays are unable to measure them [95]. There are also reports of endothelial cell and smooth muscle cell activation by DSAs alone in in-vitro studies thereby suggesting complement-independent mechanisms may contribute to chronic endothelial cell damage [96,97]. The treatment and prevention of CAMR therefore continues to be a challenge.…”
Section: Chronic Amr (Camr)mentioning
confidence: 99%